The Influence of Social Media Marketing and Influencer Marketing on Consumen Behaviour (Case Study of Gen-Z In Kota Depok, West Java) - Hadi Wijaya; Nora Listiana; Feri Nugroho; Revita Desi Hertin; Nurul Aslamiah Istiqomah; Alfi Maghfuriyah; Febria Anjara (Neo Journal of economy and social humanities, 2024)
This study examines the influence of Social Media Marketing (SMM) and Influencer Marketing on the consumer behavior of Generation Z (Gen Z) in Depok City, West Java. Utilizing a quantitative research approach, data were collected from 100 respondents through an online questionnaire. The findings from the multiple linear regression analysis indicate that both Social Media Marketing and Influencer Marketing significantly affect consumer behavior. Social Media Marketing, which is measured through variables such as content engagement, brand awareness, interactive features, and ad recall, has been shown to increase consumer engagement and influence purchasing decisions among Gen Z. Meanwhile, Influencer Marketing, which encompasses trust in influencers, influencer credibility, purchase intention, and content quality, plays a critical role in shaping the attitudes and behaviors of Gen Z consumers, leading to increased brand loyalty and purchase intentions. The study's coefficient of determination (R²) value of 78.1% suggests that these variables collectively explain the majority of the variability in consumer behavior among Gen Z in Depok City. These results align with previous research, underscoring the effectiveness of digital marketing strategies in shaping consumer behavior and offering valuable insights for businesses targeting Gen Z through social media and influencer channels.